2020
DOI: 10.3390/cells9030639
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Smooth Muscle Cell-Derived Exosomal MicroRNAs Regulate Endothelial Cell Migration Under PDGF Stimulation

Abstract: Intercellular communication between vascular smooth muscle cells (VSMCs) and endothelial cells (ECs) is essential for the maintenance of vascular homeostasis. The presence of exosomes, a recently discovered player in vascular cell communication, has been associated with vascular disease progression. However, the detailed mechanism of how the signal mediated by exosomes affects the function of vascular cells during vascular pathogenesis is yet to be further understood. In this study, we investigated the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 42 publications
0
14
0
1
Order By: Relevance
“…BMP4 treatment increased miR-101 levels by approximately 5-fold ( Figure 2 A). miR-21 and miR-486, the miRNAs whose expression is stimulated by BMP signaling or platelet-derived growth factor (PDGF) signaling, respectively, were included as controls [ 21 , 27 ]. As expected, miR-21 levels were increased, while miR-486 levels were unaffected by BMP4 treatment.…”
Section: Resultsmentioning
confidence: 99%
“…BMP4 treatment increased miR-101 levels by approximately 5-fold ( Figure 2 A). miR-21 and miR-486, the miRNAs whose expression is stimulated by BMP signaling or platelet-derived growth factor (PDGF) signaling, respectively, were included as controls [ 21 , 27 ]. As expected, miR-21 levels were increased, while miR-486 levels were unaffected by BMP4 treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results on endothelial migratory activity were described in artery endothelial cells (PAECs) exposed to PDGF stimulated VSMCs-derived exosomes. Downregulation of miR-1246, miR-182, and miR-486 in vascular smooth muscle´s exosomes promote endothelial migration [ 91 ]. Moreover, VSMCs secrete exosomes that promote vascular calcification under calcium stress triggers [ 92 , 93 ].…”
Section: Ec–vsmc Communicationmentioning
confidence: 99%
“…VSMC-derived exosomes are novel critical regulators of vascular hemostasis 150 , 151 . miR-1246 , miR-182 , and miR-486 in VSMC-derived exosomes play essential roles in the maintenance of vascular homeostasis 152 . Numerous studies have shown that proliferation, phenotype switching (mainly contractile to migratory state), apoptosis, and calcification of VSMCs are closely linked to the onset and progression of atherosclerosis 153 - 155 .…”
Section: Exosomes In Atherogenesismentioning
confidence: 99%